Multi-band high-frequency antenna for satellite, automotive radar, and 6G communication - Swati Varun Yadav; Manish Varun Yadav; Dinesh Yadav; Gaurav Kumar Soni (Scientific Reports)
Abstract This paper presents the design and development of a compact multi-band high-frequency antenna tailored for millimeter-wave applications, particularly within the 6G frequency range. The antenna features a small footprint of 10 × 12 × 1.5 mm2 and is designed using advanced electromagnetic simulations in CST Microwave Studio. Fabrication was carried out on an FR4 substrate, selected for its favorable properties at high frequencies. The antenna demonstrates an exceptionally wide impedance bandwidth of approximately 166%, covering a broad frequency range from 9.1 GHz to 100 GHz with a central frequency near 45.45 GHz. It exhibits stable radiation characteristics across the operating band, achieving a peak gain of 7.95dBi and an overall efficiency of 85%. Its miniaturized form factor and broad operational range make it a strong candidate for a wide spectrum of applications, including X-band radar, Ku-band satellite communications, K-band sensing, Ka-band 5G systems, V-band short-range wireless, W-band automotive radar, and future technologies such as 6G and security imaging systems.